Cytogenotoxic evaluations of leaves and stems extracts of Rubus rosifolius in primary metabolically noncompetent cells - de Quadros, Ana Paula Oliveira [UNESP]; Baraldi, Isabel Bragança [UNESP]; Petreanu, Marcel; Niero, Rivaldo; Mantovani, Mario Sergio; De Mascarenhas Gaivão, Isabel O’Neill; Maistro, Edson Luis [UNESP] (Taylor & Francis, 2023)
Plants with medicinal potential may also produce adverse effects in humans. This seems to be the case for the species Rubus rosifolius, where preliminary studies demonstrated genotoxic effects attributed to extracts obtained from leaves and stems of this plant using on HepG2/C3A human hepatoma cells as a model. Considering the beneficial properties of this plant as an antidiarrheal, analgesic, antimicrobial, and antihypertensive and its effects in the treatment of gastrointestinal diseases, the present study was developed with the aim of determining the cytotoxic and genotoxic potential of extracts of leaves and stems of R. rosifolius in primary without metabolic competence in human peripheral blood mononuclear cells (PBMC). Cell viability analyses at concentrations of between 0.01 and 100 µg/ml of both extracts did not markedly affect cell viability. In contrast, assessment of the genotoxic potential using the comet assay demonstrated significant damage to DNA within PBMC from a concentration of 10 µg/ml in the stem extract, and a clastogenic/aneugenic response without cytokinesis-block proliferation index (CBPI) alterations at concentrations of 10, 20, or 100 µg/ml for both extracts. Under our experimental conditions, the data obtained demonstrated genotoxic and mutagenic effects attributed to extracts from leaves and stems of R. rosifolius in cells in the absence of hepatic metabolism.
Keywords: comet assay; genotoxicity of Rubus rosifolius; micronucleus test; mutagenicity of Rubus rosifolius; Rosaceae